Single-Nucleotide Polymorphisms Associated With Age-Related Macular Degeneration and Lesion Phenotypes in the Comparison of Age-Related Macular Degeneration Treatments Trials - Maguire, Maureen G. (JAMA Ophthalmol, 2016)
IMPORTANCE: Single-nucleotide polymorphisms (SNPs) associated with the CFH, ARMS2, C3, LIPC, CFB, and C2 genes are associated with age-related macular degeneration (AMD); however, the association of these SNPs with angiographic features of neovascular AMD has been inconsistent in previous studies, and to date, no studies have addressed their association with features on optical coherence tomography. OBJECTIVE: To evaluate the influence of genotype of SNPs previously associated with AMD on the phenotype of neovascular lesions. DESIGN, SETTING, AND PARTICIPANTS: Participants for this cross-sectional study were recruited from the 1185 patients enrolled in the Comparison of Age-Related Macular Degeneration Treatments Trials (CATT), a randomized clinical trial. Eligibility criteria for CATT specified that eyes have choroidal neovascularization and visual acuity between 20/25 and 20/320. A subgroup of 835 patients provided blood samples from July 2010 through September 2011 and were genotyped for the SNPs rs1061170 (CFH), rs10490924 (ARMS2), rs2230199 (C3), rs10468017 (LIPC), rs4151667 (CFB), rs547154 (C2) using TaqMan SNP genotyping assays. Data analysis was initiated in November 2013 and completed in January 2016. MAIN OUTCOMES AND MEASURES: Pretreatment ocular characteristics on fluorescein angiography (lesion type, area of neovascularization and total lesion, retinal angiomatous proliferation) and on time-domain optical coherence tomography (presence of intraretinal, subretinal, and subretinal pigment epithelium fluid; thickness at the foveal center of the retina, subretinal fluid, and subretinal tissue complex), visual acuity, and age. RESULTS: A total of 835 (73%) of 1150 CATT patients were genotyped. Mean age decreased with the number of risk alleles for CFH (P < .001), ARMS2 (P < .001), and C3 (P = .005). The following results were found as the number of risk alleles increased from 0 to 1 to 2. For CFH, mean total thickness decreased from 476 to 476 to 434 μm (P = .01; adjusted for age, sex, and smoking status). For ARMS2, the mean area of the total lesion increased from 2.0 to 2.8 to 2.4 mm(2) (P = .03), the proportion with retinal angiomatous proliferation lesions increased from 8% to 10% to 12% (P = .05), and the proportion with intraretinal fluid increased from 72% to 71% to 82% (P = .008). For C3, the proportion with intraretinal fluid decreased from 78% to 69% to 64% (P = .001), and the mean retinal thickness decreased from 225 to 207 to 197 μm (P = .02). CONCLUSIONS AND RELEVANCE: CFH, ARMS2, and C3 were associated with specific features of neovascularization at the time patients were enrolled in CATT. Previously identified associations of ARMS2 and CFH with type of choroidal neovascularization on fluorescein angiography were not confirmed. New associations with OCT features identified in CATT need confirmation to establish whether a true association exists. TRIAL: REGISTRATION clinicaltrials.gov Identifier: NCT00593450.